USE OF INNOVATIVE METHODS IN MUSIC LESSONS - Кулічова, С.М.; Шевчук, П.Г. (Modern engineering and innovative technologies, 2023)
The article reveals the essence of the concepts "innovation", "innovative activity of a music teacher"; the content of the innovative activity of the music teacher as a component of his professional training is considered. Innovative methods, techniques,